1967
DOI: 10.33584/jnzg.1967.29.1242
|View full text |Cite
|
Sign up to set email alerts
|

Pasture Species for Northland

Abstract: UNDER the usual management system, pasture surpluses are converted into fodder for feeding in periods of shortage, and sheep or cattle are grazed on pastures most of the year. It is this type of management which influences the present evaluation of pasture species. Whether this outlook is to continue is debatable, but it can be said that the potential production of many species is rarely achieved in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Earlier trials at Kaikohe (Lambert 1967) showed Ariki ryegrass and S170 tall fescue to be similar in growth and persistence on the volcanic soil. As Ariki failed to persist, perhaps for reasons outlined by Harris et al (1977), Nui rye grass had to be used for the ryegrass comparison between soil types.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier trials at Kaikohe (Lambert 1967) showed Ariki ryegrass and S170 tall fescue to be similar in growth and persistence on the volcanic soil. As Ariki failed to persist, perhaps for reasons outlined by Harris et al (1977), Nui rye grass had to be used for the ryegrass comparison between soil types.…”
Section: Discussionmentioning
confidence: 99%
“…Growth rates of pastures containing paspalum have been measured in many trials in Northland and Waikato. However, except for Lynch (1953), results have been published on a seasonal basis (Karlovsky 1959;Lambert 1967;Parker 1970;Baars 1976), or remain unpublished. Results of the survey support growth patterns measured by Lynch (1953), and work at Grasslands Division, DSIR, Kaikohe.…”
Section: Growth and 'Use Of Paspulurnmentioning
confidence: 99%
“…These effects are probably not peculiar to browntop but the extent of these effects produced by other gras,ses is not well undersitowd. Mouat and Walker (1959)) using glasshouse studies, concluded that browntop was a stronger competitor for P than was ryegrass or cocksfoot, and Lambert (1967) found ,at Kaikohe that rye= grass reduced the moisture conteot of the topsoil much mart than did paspalum or K'ikuyu grass.…”
Section: P a Vailable To C Lovermentioning
confidence: 99%